Identification of Distinct Arterial Waveform Clusters and a Longitudinal Evaluation of Their Clinical Usefulness. Issue 4 (October 2019) - Sluyter, John D.; Hughes, Alun D.; Camargo, Carlos A.; Thom, Simon A. McG.; Parker, Kim H.; Hametner, Bernhard; Wassertheurer, Siegfried; Scragg, Robert
Abstract : Clustering of arterial blood pressure (BP) waveform parameters could summarize complex information into distinct elements, which could be used to investigate cumulative (nonredundant) associations. We investigated this hypothesis in a large, adult population-based study (ViDA trial [Vitamin D Assessment] trial). To interpret the clusters and evaluate their usefulness, we examined their predictors and associations with cardiovascular events. In 4253 adults (mean age 65 years; 55% male) without a prior cardiovascular event, suprasystolic oscillometry was performed, yielding aortic pressure waveforms and several hemodynamic parameters. Participants were followed up for 4.6 years (median), accruing 300 cardiovascular events. Principal component analysis reduced 14 arterial waveform parameters to 3 uncorrelated factors that together explained 90% of the variability of the original data. Factors 1, 2, and 3 appeared to represent BP pulsatility, mean BP, and wave reflection, respectively. Across 6 antihypertensive drug classes, there were no differences in brachial systolic ( P =0.23) and diastolic ( P =0.13) BP; but there were significant variations in factor 3 ( P <0.0001), especially for β-blocker use. The first and third factors were positively associated with cardiovascular events (multivariable-adjusted standardized hazard ratio [95% CI]=1.33 [1.18–1.50] and 1.15 [1.02–1.30], respectively), whereas the second factor had a J-shaped relationship, with a nadir corresponding to a brachial diastolic BP of ≈75 mm Hg. In conclusion, BP pulsatility, mean BP, and wave reflection are prognostically meaningful, distinct aspects of arterial function that can be used to summarize physiological variations in multiple arterial waveform parameters and identify truly cumulative associations when used as cardiovascular risk outcomes. Abstract : Supplemental Digital Content is available in the text.